Spatial Tactics in Criminal Courts and the Politics of Legal Technicalities. Issue 5 (14th July 2015) - Sylvestre, Marie‐Eve; Damon, William; Blomley, Nicholas; Bellot, Céline
Abstract This paper documents court‐imposed bail and sentencing conditions with spatial dimensions, such as red zones, no contact conditions, curfews and prohibitions to demonstrate, issued in the context of criminal proceedings. These conditional orders, which are growing in importance and have a significant impact on the lives of marginalized groups of people, have not received the attention they deserve in the literature. As opposed to better publicized forms of spatial regulation such as legislation or policing strategies, these conditional orders are a distinctive form of spatial tactic that rely on ancient and routinized rules of criminal procedure and the practices of the courts. In order to understand this spatial tactic, and its impact on marginalized people's rights and uses of spaces, we argue that it is necessary to pay attention to the legal rationalities, knowledge and practices that sustain them.